Composite material with heterostructure, preparation method of composite material, and preparation method and application of composite material positive electrode
The conductive polymer intercalated vanadium pentoxide was prepared by ball milling method and Ag nanocrystals were modified. Self-supported electrodes were prepared in combination with single-wall carbon nanotubes, which solved the problem of insufficient zinc storage capacity of vanadium pentoxide, and achieved high magnification and long cycles. Performance, reduces costs and improves the performance of zinc ion batteries.
Patent Information
- Application Number
- CN202411284956.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing vanadium pentoxide has insufficient zinc storage capacity in zinc-ion batteries, resulting in poor performance. The use of non-conductive additives and current collectors during the preparation of traditional coating methods limits electron/ion transport, increasing costs and reducing energy density.
The conductive polymer intercalated vanadium pentoxide was prepared by ball milling method, and a heterostructure composite material was formed by Ag nanocrystal modification, which expanded the layer spacing and improved conductivity, and prepared a self-supporting electrode in combination with single-wall carbon nanotubes.
It achieves high magnification and long cycle performance, reduces material synthesis costs, improves the specific capacity and Coulomb efficiency of zinc ion batteries, improves the uniformity and dispersion of electrode materials, and has good application prospects.
Smart Images

Figure CN119153650A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode composite materials, and in particular to a composite material with a heterogeneous structure, a preparation method, a preparation method of a composite material positive electrode and applications. Background Art
[0002] Lithium-ion batteries are widely used in consumer electronics, electric vehicles and other fields due to their advantages such as high energy density and long cycle life. However, the greater safety hazards and high production costs have greatly limited their application in large-scale energy storage. Therefore, the development of other types of secondary batteries that are cheap, highly safe and environmentally friendly as alternatives to lithium-ion batteries is in line with the requirements of the sustainable development strategy. Replacing organic electrolytes with aqueous electrolytes can not only reduce the cost of battery production, but also improve safety. Among many aqueous secondary batteries, aqueous zinc-ion batteries have a low standard redox potential (0.76 V) and a high theoretical mass / volume capacity (820 mAh g -1 / 5855 mAh cm -3 ), high hydrogen evolution overpotential, abundant resources and secondary processing are considered to be ideal green battery systems. However, there is a strong electrostatic interaction between the highly polar divalent zinc ions and the lattice of the positive electrode material, which makes the diffusion kinetics of zinc ions in the positive electrode material slow, resulting in low capacity and poor rate / cycle performance.
[0003] Vanadium pentoxide has the advantages of high theoretical capacity (multiple electron transfer characteristics) and open structure, and is regarded as a highly promising cathode material for aqueous zinc-ion batteries. However, commercial vanadium pentoxide often has poor high-rate performance and long-cycle stability due to its shortcomings such as small interlayer spacing, low electronic conductivity, strong localization of zinc ions in the crystal structure, and structural degradation during the cycle. In order to improve the zinc storage performance of vanadium pentoxide, many researchers have carried out a lot of modification research work to address its shortcomings. Guest pre-intercalation to expand the interlayer spacing of vanadium oxide compounds is an effective strategy to improve the diffusion kinetics of zinc ions. For example, Li et al. synthesized polyaniline (PANI) intercalated V2O5 nanosheets (PVO). The enlarged interlayer spacing and the high conductivity of the polymer improve the electron / ion transport performance and structural integrity of the cathode material, thereby showing excellent high-rate performance and ultra-long cycle life. In addition, studies have shown that the synergistic effect of heterostructures can stimulate charge transfer and redistribution at heterogeneous interfaces, improve electron transport properties, and induce built-in electric fields to reduce ion diffusion barriers and improve ion diffusion kinetics, thereby improving the specific capacity and rate performance of electrode materials. For example, the team of Professor Wu Zhongshuai of the University of Chinese Academy of Sciences constructed a 2D / 2D van der Waals heterostructure composite material (A-V2O5 / G) by uniformly growing V2O5 nanosheets on graphene. As the positive electrode of aqueous zinc-ion batteries, it exhibited high specific capacity and ultra-high rate performance. Zhang et al. prepared a van der Waals heterojunction composed of carbon quantum dots and V2O5 nanobelts by a simple one-step hydrothermal method. Although these methods can improve the zinc storage capacity of vanadium pentoxide, the material synthesis has high equipment requirements, harsh conditions and cumbersome processes. On the other hand, the positive electrodes of zinc-ion batteries in the above reports were all prepared by traditional coating methods. The use of non-conductive additives and current collectors in the preparation process not only limits electron / ion transport, but also increases costs and reduces energy density. Summary of the invention
[0004] The purpose of the invention is to provide a heterogeneous structure composite material, a preparation method, a preparation method of a composite material positive electrode and application, which solves the problem that the method for improving the zinc storage capacity of vanadium pentoxide in the prior art is difficult and the positive electrode material performance is poor.
[0005] The present invention is achieved by a method for preparing a composite material with a heterogeneous structure, the preparation method comprising the following steps: Step 1: sequentially adding a solvent, vanadium pentoxide and a monomer of a conductive polymer into a ball milling device for ball milling to obtain vanadium pentoxide intercalated into the conductive polymer; Step 2: Add the conductive polymer intercalated with vanadium pentoxide obtained in step 1 into a solvent, mix well, and then add silver nitrate solution and a reducing agent in sequence to obtain a composite material with a heterogeneous structure consisting of Ag nanocrystal-modified conductive polymer intercalated with vanadium pentoxide.
[0006] The heterogeneous structure composite material of the present invention is composed of highly conductive Ag nanocrystals and conductive polymer intercalated vanadium pentoxide. On the one hand, the conductive polymer pre-intercalation can effectively expand the interlayer spacing of vanadium pentoxide, providing a rapid transportation channel for zinc ion insertion / extraction, and on the other hand, the Ag nanocrystal modification can improve the conductivity of the composite material, so the heterogeneous structure composite material has good electrochemical zinc storage performance. The Ag nanocrystal modified conductive polymer intercalated vanadium pentoxide constitutes a heterogeneous structure composite material with simple synthesis process, low cost, high yield, good repeatability, excellent rate / cycle performance, and good application prospects.
[0007] A further technical solution of the present invention is: in the step 1, ball milling is performed for 120-180 hours to obtain wet material of conductive polymer intercalated vanadium pentoxide, and the wet material is collected and processed to obtain conductive polymer intercalated vanadium pentoxide.
[0008] A further technical solution of the present invention is: the specific steps of collecting and processing the wet material in step 1 are: washing the wet material with deionized water and freeze-drying it.
[0009] A further technical solution of the present invention is: in the step 1, the solvent is deionized water, and the ball milling equipment is a ball milling tank.
[0010] A further technical solution of the present invention is: in the step 1, the conductive polymer is at least one of poly (3,4-ethylenedioxythiophene) and polyaniline.
[0011] A further technical solution of the present invention is: in the step 2, the conductive polymer intercalated vanadium pentoxide obtained in the step 1 is added to deionized water, mixed evenly and then transferred to a water bath at 25°C-80°C, silver nitrate solution and a reducing agent are added in sequence and stirred for 5 minutes-60 minutes, and the Ag nanocrystal-modified conductive polymer intercalated vanadium pentoxide composite material with a heterogeneous structure is collected.
[0012] A further technical solution of the present invention is: the collecting step in step 2 is: washing with deionized water and freeze-drying.
[0013] A further technical solution of the present invention is: in the step 2, the intercalated vanadium pentoxide of the conductive polymer is added to deionized water, ultrasonicated for 20 minutes to 40 minutes, and stirred for 20 minutes to 40 minutes to obtain a uniform dispersion, and a silver nitrate solution and a reducing agent are added dropwise to the dispersion.
[0014] A further technical solution of the present invention is: the reducing agent in step 2 is a sodium citrate solution.
[0015] The second aspect of the present invention discloses a composite material with a heterogeneous structure, which is obtained by the above-mentioned preparation method.
[0016] The third aspect of the present invention discloses a method for preparing a heterostructured composite material positive electrode, comprising the following steps: dispersing the composite material and single-walled carbon nanotubes in an organic solvent by cell crushing, ultrasound and stirring, then adding the single-walled carbon nanotube dispersion dropwise into the heterostructured composite material dispersion, ultrasonically stirring and mixing evenly, and finally preparing a self-supporting electrode by vacuum filtration / freeze drying.
[0017] A further technical solution of the present invention is: the organic solvent is N-methylpyrrolidone or N,N-dimethylformamide, and the mass ratio of the composite material to the single-walled carbon nanotube is (8-10):1.
[0018] Finally, the present invention discloses an application of a heterogeneous structure composite material positive electrode. The positive electrode is obtained by adopting a preparation method of a heterogeneous structure composite material positive electrode and is applied to an aqueous zinc ion battery.
[0019] Beneficial effects of the present invention: The present invention develops a method for preparing an aqueous zinc ion battery positive electrode based on vanadium pentoxide, which has simple process, low cost, high yield and good repeatability, and obtains a zinc ion battery positive electrode material with good rate / cycle performance and high coulomb efficiency. The prepared product has excellent performance after electrochemical performance test; The conductive polymer inserted into the layered vanadium pentoxide in the composite material prepared by the present invention greatly increases the interlayer spacing of the (001) crystal plane, which is conducive to the rapid insertion / extraction of zinc ions; the heterogeneous structure synergistic effect can induce heterogeneous interface charge transfer and redistribution, thereby improving the electronic transport performance of the composite material; Ag nanocrystals can effectively inhibit the agglomeration of PVO materials. The Ag nanocrystal modified conductive polymer intercalated with vanadium pentoxide prepared by the present invention has good uniformity and dispersibility, and the material synthesis process is simple, low cost, high yield and good repeatability.
[0020] The positive electrode prepared by vacuum filtration / freeze drying of Ag nanocrystal-modified conductive polymer intercalated with vanadium pentoxide to form a heterostructure composite material and single-walled carbon nanotubes has good flexibility and has application potential in wearable electronic devices. Moreover, the positive electrode of the heterostructure composite material prepared by the present invention has high specific capacity, good rate and cycle performance, and high coulomb efficiency, which can effectively improve the current problems of low specific capacity, low coulomb efficiency, poor rate performance and short cycle life of the positive electrode of vanadium-based zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 1 is the XRD pattern of the heterostructure composite material obtained in Example 1.
[0022] Figure 2 This is the Raman graph of the heterostructure composite material obtained in Example 1.
[0023] Figure 3 TEM images of the heterostructure composite material obtained in Example 1 at different magnifications.
[0024] Figure 4 TEM-EDS image of the heterostructure composite material obtained in Example 1.
[0025] Figure 5 A diagram showing different bending states of the self-supporting electrode.
[0026] Figure 6 This is the rate performance diagram of the self-supporting electrode.
[0027] Figure 7 For a self-supporting electrode at 1Ag -1 The cycle performance diagram below. DETAILED DESCRIPTION
[0028] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0029] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.
[0030] A method for preparing a composite material with a heterogeneous structure comprises the following steps: 1) adding deionized water, vanadium pentoxide and a conductive polymer monomer into a ball mill in sequence, and preparing the conductive polymer intercalated vanadium pentoxide by high-energy ball milling in-situ polymerization and intercalation reaction; 2) adding the conductive polymer intercalated vanadium pentoxide obtained in step 1) into deionized water, stirring ultrasonically to obtain a uniform dispersion, then adding silver nitrate solution and sodium citrate solution dropwise, and preparing Ag nanocrystal-modified conductive polymer intercalated vanadium pentoxide to form a heterostructure composite material by water bath chemical reduction.
[0031] A further technical solution is that the vanadium pentoxide and the conductive polymer monomer in 1) are both commercial materials, and the materials used in the synthesis method are selected from Shanghai MacLean Biochemical Technology Co., Ltd.
[0032] A further technical solution is that the step 1) specifically includes the following steps: adding deionized water, vanadium pentoxide and conductive polymer monomer into a ball mill, ball milling for 144 hours to obtain conductive polymer intercalated vanadium pentoxide, then washing with deionized water, and freeze-drying to collect the product.
[0033] A further technical solution is that the step 2) specifically includes the following steps: adding the vanadium pentoxide intercalated with the conductive polymer to deionized water and stirring it ultrasonically to obtain a uniform dispersion, and adding sodium citrate and silver nitrate to the deionized water and stirring them to obtain a uniform dispersion; then transferring the vanadium pentoxide dispersion intercalated with the conductive polymer to a water bath, adding the silver nitrate solution and the sodium citrate solution dropwise, and stirring for a period of time to obtain a heterogeneous structure composite material composed of Ag nanocrystal-modified conductive polymer intercalated with vanadium pentoxide; and finally collecting the material by washing with deionized water and freeze-drying.
[0034] The composite material is denoted as Ag-PVO, where PVO stands for conducting polymer intercalated vanadium pentoxide.
[0035] A further technical solution is that the conductive polymer is one or more of poly (3,4-ethylenedioxythiophene), polyaniline and the like.
[0036] Poly (3,4-ethylenedioxythiophene) is represented by PEODT, and polyaniline is represented by PANI.
[0037] A further technical solution is that in step 1), the mass of vanadium pentoxide is 0.7-14 g, the amount of conductive polymer monomer is 0.3-6 mL, and the amount of deionized water is 60 mL; in step 2), the mass of the heterostructure composite material is 0.19 g-0.95 g, the mass of silver nitrate is 0.017 g-0.085 g, and the mass of sodium citrate is 0.025 g-0.125 g.
[0038] A further technical solution is that the ball milling time in step 1) is 144 hours; the ultrasonic and stirring times to obtain the dispersion in step 2) are 30 minutes each, and the water bath stirring chemical deposition time is 5 minutes to 60 minutes.
[0039] Preferably, a further technical solution is that the water bath temperature in step 2) is from room temperature to 70°C.
[0040] The present invention provides a method for preparing a positive electrode of a heterogeneous structure composite material, wherein the Ag nanocrystal-modified conductive polymer intercalated with vanadium pentoxide is used to form a heterogeneous structure composite material, and the method is vacuum filtered / freeze dried to prepare a positive electrode of a zinc ion battery. More specifically, the method comprises the following steps: the heterogeneous structure composite material and single-walled carbon nanotubes are dispersed in an organic solvent by cell crushing, ultrasonication, and stirring, and then the single-walled carbon nanotube dispersion is dropwise added to the heterogeneous structure composite material dispersion, and ultrasonic stirring is performed to mix uniformly, and finally a self-supporting electrode is prepared by vacuum filtration / freeze drying.
[0041] Ag nanocrystals modified conductive polymer intercalated with vanadium pentoxide to form a heterostructure composite material and single-walled carbon nanotubes were composited through vacuum filtration / freeze drying to make a self-supporting electrode, denoted as Ag-PVO self-supporting electrode.
[0042] A further technical solution is that the organic solvent selected for the heterogeneous structure composite material and the single-walled carbon nanotube dispersion is one of N-methylpyrrolidone (NMP) and N,N-dimethylformamide.
[0043] A further technical solution is that the heterogeneous structure composite material and the single-walled carbon nanotubes are dispersed in an organic solvent, the cell crushing ultrasound and stirring time are 30 minutes each, and the two are evenly mixed with ultrasound and stirring time for 30 minutes each.
[0044] A further technical solution is that the mass ratio of the heterostructure composite material composed of Ag nanocrystals modified conductive polymer intercalated with vanadium pentoxide and single-walled carbon nanotubes in the electrode is 9:1.
[0045] The specific experiment is shown in the following examples: Example 1
[0046] This embodiment provides a method for preparing a heterogeneous structure composite material for an aqueous zinc ion battery, the steps are as follows: In the first step, 60 mL of deionized water, 800 mg of commercial vanadium pentoxide and 0.3 mL of 3,4-ethylenedioxythiophene were added to a ball mill in sequence at room temperature and ball milled for 144 h. The obtained PVO material was washed with deionized water and collected by freeze drying.
[0047] In the second step, 190 mg of PVO was weighed and added to deionized water to prepare a 1 mg / mL solution, and ultrasonic stirring was performed for 30 minutes each to obtain a uniform dispersion; 0.017 g of silver nitrate and 0.025 g of sodium citrate were respectively added to deionized water and stirred to prepare a 1 mg / mL solution; the PVO solution was transferred to a water bath, and the silver nitrate solution and the sodium citrate solution were added dropwise in turn, stirred at 70°C for 5 minutes, then washed with deionized water, and the Ag-PVO heterostructure composite material was collected by freeze drying.
[0048] Figure 1 The XRD pattern of the heterostructure composite material obtained in the embodiment is shown in FIG. As can be seen from the figure, the interlayer spacing of vanadium pentoxide (002) is large, indicating that the conductive polymer is inserted into the interlayer, which is conducive to the rapid insertion / extraction of zinc ions; no obvious Ag characteristic peak is observed in the XRD spectrum, which may be mainly due to the small size and low content of Ag nanocrystals.
[0049] Figure 2 The Raman graph of the heterostructure composite material obtained in the example shows that the conductive polymer PEDOT exists in the composite material.
[0050] Figure 3 TEM images of the heterostructure composite material obtained in the embodiment at different magnifications. It can be observed from the figure that the heterostructure composite material is composed of Ag nanocrystals and vanadium pentoxide intercalated with sheet-like PEDOT. Among them, the diameter of the Ag nanocrystal is about 10-35nm, and it is evenly distributed on the surface of the conductive polymer intercalated vanadium pentoxide, which can effectively improve the conductivity of the composite material.
[0051] Figure 4 TEM-EDS image of the heterostructure composite material obtained in the example, the results show the presence of elements such as Ag, V, O, S, and C in the composite material. Example 2
[0052] This embodiment provides a method for preparing a heterogeneous structure composite material for an aqueous zinc ion battery, comprising the following steps: In the first step, 60 mL of deionized water, 16 g of commercial vanadium pentoxide and 6 mL of 3,4-ethylenedioxythiophene were added to a ball mill in sequence at room temperature and ball milled for 144 h. The obtained PVO material was washed with deionized water and collected by freeze drying.
[0053] In the second step, 190 mg of PVO was weighed and added to deionized water to prepare a 1 mg / mL solution, and ultrasonic stirring was performed for 30 minutes each to obtain a uniform dispersion; 0.017 g of silver nitrate and 0.025 g of sodium citrate were respectively added to deionized water and stirred to prepare a 1 mg / mL solution; the PVO solution was transferred to a water bath, and the silver nitrate solution and the sodium citrate solution were added dropwise in turn, stirred at 70°C for 5 minutes, then washed with deionized water, and the Ag-PVO heterostructure composite material was collected by freeze drying. Example 3
[0054] This embodiment provides a method for preparing a heterogeneous structure composite material for an aqueous zinc ion battery, comprising the following steps: In the first step, 60 mL of deionized water, 800 mg of commercial vanadium pentoxide and 0.3 mL of 3,4-ethylenedioxythiophene were added to a ball mill in sequence at room temperature and ball milled for 144 h. The obtained PVO material was washed with deionized water and collected by freeze drying.
[0055] In the second step, 950 mg of PVO was weighed and added to deionized water to prepare a 2 mg / mL solution, and ultrasonic stirring was performed for 30 minutes each to obtain a uniform dispersion; 0.085 g of silver nitrate and 0.125 g of sodium citrate were respectively added to deionized water and stirred to prepare a 2 mg / mL solution; the PVO solution was transferred to a water bath, and the silver nitrate solution and the sodium citrate solution were added dropwise in turn, stirred at 70°C for 5 minutes, then washed with deionized water, and the Ag-PVO heterostructure composite material was collected by freeze drying. Example 4
[0056] This embodiment provides a method for preparing a heterogeneous structure composite material for an aqueous zinc ion battery, comprising the following steps: In the first step, 60 mL of deionized water, 800 mg of commercial vanadium pentoxide and 0.3 mL of 3,4-ethylenedioxythiophene were added to a ball mill in sequence at room temperature and ball milled for 144 h. The obtained PVO material was washed with deionized water and collected by freeze drying.
[0057] In the second step, 190 mg of PVO was weighed and added to deionized water to prepare a 2 mg / mL solution, and ultrasonic stirring was performed for 30 minutes each to obtain a uniform dispersion; 0.017 g of silver nitrate and 0.025 g of sodium citrate were respectively added to deionized water and stirred to prepare a 2 mg / mL solution; the PVO solution was transferred to a water bath, and the silver nitrate solution and the sodium citrate solution were added dropwise in turn, stirred at 70°C for 5 minutes, then washed with deionized water, and the Ag-PVO heterostructure composite material was collected by freeze drying. Example 5
[0058] This embodiment provides a method for preparing a heterogeneous structure composite material for an aqueous zinc ion battery, comprising the following steps: In the first step, 60 mL of deionized water, 800 mg of commercial vanadium pentoxide and 0.3 mL of 3,4-ethylenedioxythiophene were added to a ball mill in sequence at room temperature and ball milled for 144 h. The obtained PVO material was washed with deionized water and collected by freeze drying.
[0059] In the second step, 190 mg of PVO was weighed and added to deionized water to prepare a 1 mg / mL solution, and ultrasonic stirring was performed for 30 minutes each to obtain a uniform dispersion; 0.017 g of silver nitrate and 0.025 g of sodium citrate were respectively added to deionized water and stirred to prepare a 1 mg / mL solution; the PVO solution was transferred to a water bath, and the silver nitrate solution and the sodium citrate solution were added dropwise in turn, stirred at room temperature for 5 minutes, then washed with deionized water, and the Ag-PVO heterostructure composite material was collected by freeze drying. Example 6
[0060] This embodiment provides a method for preparing a heterogeneous structure composite material for an aqueous zinc ion battery, comprising the following steps: In the first step, 60 mL of deionized water, 800 mg of commercial vanadium pentoxide and 0.3 mL of 3,4-ethylenedioxythiophene were added to a ball mill in sequence at room temperature and ball milled for 144 h. The obtained PVO material was washed with deionized water and collected by freeze drying.
[0061] In the second step, 190 mg of PVO was weighed and added to deionized water to prepare a 1 mg / mL solution, and ultrasonic stirring was performed for 30 minutes each to obtain a uniform dispersion; 0.017 g of silver nitrate and 0.025 g of sodium citrate were respectively added to deionized water and stirred to prepare a 1 mg / mL solution; the PVO solution was transferred to a water bath, and the silver nitrate solution and the sodium citrate solution were added dropwise in turn, stirred at 70°C for 60 minutes, then washed with deionized water, and the Ag-PVO heterostructure composite material was collected by freeze drying.
[0062] Experimental verification has shown that any one of the stirring time, ultrasonic time, heating temperature, drying time and related parameters in the preparation method of the present invention within the range of the claims can synthesize Ag nanocrystal-modified conductive polymer intercalated with vanadium pentoxide to form a heterogeneous structure composite material, with only slight differences in structure and performance. Example 7
[0063] A method for preparing a heterogeneous composite material positive electrode, characterized in that it includes the following steps: the composite material prepared in Example 1 and the single-walled carbon nanotubes are uniformly dispersed in an NMP solution by cell crushing, ultrasound, stirring, and then the Ag-PVO dispersion is dropwise added to the single-walled carbon nanotube dispersion, stirred and mixed uniformly, and then vacuum filtered / freeze dried to prepare a self-supporting electrode. The self-supporting electrode does not require additives such as PVDF and carbon black, and has good flexibility.
[0064] Figure 5 The figure shows the different bending states of the Ag-PVO self-supporting electrode, indicating that the Ag-PVO self-supporting electrode has good flexibility and anti-bending properties.
[0065] Figure 6 The rate performance diagram of the Ag-PVO self-supporting electrode shows that at 0.2, 0.5, 1, 2, 3, 5, 8, 10, 15, 20, and 30 Ag -1 At the current density, the discharge specific capacities are 518.1, 515.6, 511.6, 506.8, 502.6, 495.9, 486.8, 480.6, 458.4, 433.3, and 391.7 mAh g, respectively. -1 , indicating that the Ag-PVO self-supporting electrode has good rate performance.
[0066] Figure 7 For Ag-PVO self-supporting electrode on 1Ag -1 Cycling performance diagram under current density. It can be seen from the figure that the Ag-PVO self-supporting electrode has good cycling stability, and the capacity retention rate after 100 cycles is close to 100% (compared with the highest capacity value after activation).
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite material with a heterogeneous structure, characterized in that: The preparation method comprises the following steps: Step 1: sequentially adding a solvent, vanadium pentoxide and a monomer of a conductive polymer into a ball milling device for ball milling to obtain vanadium pentoxide intercalated into the conductive polymer; Step 2: Add the conductive polymer intercalated with vanadium pentoxide obtained in step 1 into a solvent, mix well, and then add silver nitrate solution and a reducing agent in sequence to obtain a composite material with a heterogeneous structure consisting of Ag nanocrystal-modified conductive polymer intercalated with vanadium pentoxide.
2. The method for preparing a composite material with a heterogeneous structure according to claim 1, characterized in that: In the step 1, ball milling is performed for 120-180 hours to obtain a wet material of the conductive polymer intercalated with vanadium pentoxide, and the wet material is collected and processed to obtain the conductive polymer intercalated with vanadium pentoxide.
3. The method for preparing a composite material with a heterogeneous structure according to claim 1, characterized in that: In the step 1, the conductive polymer is at least one of poly (3,4-ethylenedioxythiophene) and polyaniline.
4. The method for preparing a composite material with a heterogeneous structure according to claim 1, characterized in that: In the step 2, the conductive polymer intercalated vanadium pentoxide obtained in the step 1 is added to deionized water, mixed evenly and then transferred to a water bath at 25° C. to 80° C., and a silver nitrate solution and a reducing agent are added in sequence and stirred for 5 minutes to 60 minutes, and the composite material of the heterogeneous structure formed by the conductive polymer intercalated vanadium pentoxide modified by Ag nanocrystals is collected.
5. The method for preparing a heterogeneous structure composite material according to claim 1, characterized in that: In the step 2, the intercalated vanadium pentoxide of the conductive polymer is added to deionized water, ultrasonicated for 20 minutes to 40 minutes, and stirred for 20 minutes to 40 minutes to obtain a uniform dispersion, and a silver nitrate solution and a reducing agent are added dropwise to the dispersion.
6. The method for preparing a heterogeneous composite material according to claim 1, characterized in that: The reducing agent in the step 2 is sodium citrate solution.
7. A composite material with a heterogeneous structure, characterized in that: The method is obtained by the preparation method described in any one of claims 1 to 6.
8. A method for preparing a heterogeneous composite material positive electrode, characterized in that: The method comprises the following steps: dispersing the composite material described in claim 7 and single-walled carbon nanotubes in an organic solvent by cell crushing, ultrasound and stirring, respectively, then adding the single-walled carbon nanotube dispersion dropwise into the heterostructure composite material dispersion, mixing evenly by ultrasonic stirring, and finally making a self-supporting electrode by vacuum filtration / freeze drying.
9. The method for preparing a heterogeneous composite material positive electrode according to claim 8, characterized in that: The organic solvent is N-methylpyrrolidone or N,N-dimethylformamide, and the mass ratio of the composite material to the single-walled carbon nanotube is (8-10):
1.
10. An application of a heterogeneous composite material positive electrode, characterized in that: The positive electrode is obtained by the preparation method of claim 9 and is applied to aqueous zinc ion batteries.
Citation Information
Cited By
Preparation method of graphene quantum dot cloud wool
CN120485977A
Preparation method of amorphous vanadium oxide / nitrogen-doped carbon layered composite material
CN121355215A
